Indigenous Peoples' Rights in Data: a contribution toward Indigenous Research Sovereignty - Maui Hudson; Stephanie Russo Carroll; Stephanie Russo Carroll; Jane Anderson; Darrah Blackwater; Felina M. Cordova-Marks; Jewel Cummins; Dominique David-Chavez; Adam Fernandez; Adam Fernandez; Ibrahim Garba; Ibrahim Garba; et al. (Frontiers in Research Metrics and Analytics, 2023)
Indigenous Peoples' right to sovereignty forms the foundation for advocacy and actions toward greater Indigenous self-determination and control across a range of domains that impact Indigenous Peoples' communities and cultures. Declarations for sovereignty are rising throughout Indigenous communities and across diverse fields, including Network Sovereignty, Food Sovereignty, Energy Sovereignty, and Data Sovereignty. Indigenous Research Sovereignty draws in the sovereignty discourse of these initiatives to consider their applications to the broader research ecosystem. Our exploration of Indigenous Research Sovereignty, or Indigenous self-determination in the context of research activities, has been focused on the relationship between Indigenous Data Sovereignty and efforts to describe Indigenous Peoples' Rights in data.